Combined applications of biochar and legume residues to improve growth and yield of sweet potato in a dry land area of East Java - E D I Wilujeng; W Ningtyas; Y Nuraini (Journal of Degraded and Mining Lands Management, 2015)
Production of sweet potato in the dry land areas of East Java is low because of low levels of soil fertility in the region. One of alternatives to improve crop production in the area is the use of local sources of organic matters. The purpose of this study was to investigate the effects of combined biochar and residues of Mucuna pruriens L., Psophocarpus tetragonolobus L., Phaseolus lunatus L. and Dolichos lablab LB., on growth and yield of sweet potato in dry land area of East Java. A field experiment was conducted in the farmers' field at Gondanglegi village, Bandarkedungmulyo District of Jombang. The treatments tested were mixtures of each of four legume residues and biochar with the following proportion (% dry weight), 50%  legume residues + 50% biochar, 75% legume residues + 25% biochar, and 100% legume residues + 0% biochar. A control treatment with no application of legume residues and biochar was also included in the experiment. Each mixture of legume residues and biochar was applied in a 2 x 3 m field plot at a rate of 5 t/ha. Seedlings of a local variety of purple sweet potato were planted in each plot with a planting distance of 80 cm between rows and 30 cm in row. Thirteen treatments were arranged in a randomized block design with three replications. The results showed that after 4 months, application of combined biochar and residues of M. pruriens, P.tetragonolubus, P. lunatus, D. lablab affected soil fertility and growth of sweet potato on dry land areas. The combination of 2.5 t D. lablab residues/ha and 2.5 t biochar/ha produced the highest yield of sweet potato by 16.53 t/ ha, an increase of 347.9% when compared to the control treatment with no addition of legume residues and biochar.